2021
DOI: 10.1007/s10551-021-04933-x
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Innovation in Developing Countries

Abstract: Although corporate social innovation studies in developing countries acknowledge the importance of firm resources and capabilities for attaining social goals, they overlook the way in which these interact with broader institutions to generate successful outcomes. We address this gap by exploring the relationship between firm resources-capabilities and institutions that is conducive to meeting both business and social interests in developing countries. By employing a fuzzy-set qualitative comparative analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 82 publications
0
9
0
1
Order By: Relevance
“…As this research has been mainly conducted at the macro level (national policies and various institutional levels), the involvement of governments (in partnership with for‐profits, foundations, and research organizations) at the national, regional, and local levels promotes entrepreneurship and the growth of nascent industries (Zabala‐Iturriagagoitia, 2021). We found evidence that interactions between firms and broader institutions facilitate successful outcomes as the former's resources‐capabilities compensate for any institutional voids and enable the useful delivery of any projects aimed at addressing grand challenges (Saka‐Helmhout et al, 2021). We found that such research has foundations in the resource‐based view (RBV) and the knowledge‐based view (KBV) and institutional theories.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As this research has been mainly conducted at the macro level (national policies and various institutional levels), the involvement of governments (in partnership with for‐profits, foundations, and research organizations) at the national, regional, and local levels promotes entrepreneurship and the growth of nascent industries (Zabala‐Iturriagagoitia, 2021). We found evidence that interactions between firms and broader institutions facilitate successful outcomes as the former's resources‐capabilities compensate for any institutional voids and enable the useful delivery of any projects aimed at addressing grand challenges (Saka‐Helmhout et al, 2021). We found that such research has foundations in the resource‐based view (RBV) and the knowledge‐based view (KBV) and institutional theories.…”
Section: Resultsmentioning
confidence: 99%
“…We found that such research has foundations in the resource‐based view (RBV) and the knowledge‐based view (KBV) and institutional theories. There is also the argument that innovation policies play a key role in these activities through knowledge transfer, positive spillovers, and innovation‐oriented public procurement (Saka‐Helmhout et al, 2021; Zabala‐Iturriagagoitia, 2021). Research in this cluster is concentrated within the European continent and within the health and UAV manufacturing industry sectors.…”
Section: Resultsmentioning
confidence: 99%
“…The latter can be found in both developed (Battaglia et al, 2021) and developing economies (Crupi et al, 2022; Peerally et al, 2022). These differences might be attributed to the weak institutional environments prevalent in developing economies (Peerally et al, 2022; Saka‐Helmhout et al, 2021).…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…According to Surana, Singh & Sagar (2020), there is a need for developing a clear framework to emphasize the need of defining the start-ups' goals, coordination, embrace the performance monitoring systems and multi-phase capacity buildings. The practices in developed countries such as Italy proves that incubation and innovation start-up are significantly less in job creation although have a positive effect on increasing sales revenues in long terms and attainment of societal goals (Lukeš, Longo & Zouhar, 2019;Saka-Helmhout et al, 2021). Yet, star-ups, incubation and innovation hubs are considerable mechanisms employed in developing countries for implementing Sustainable and Development Goals (SDGs).…”
Section: Introductionmentioning
confidence: 99%